Analisis Pengembangan Pariwisata Berbasis Masyarakat Di Kawasan Agrowisata Payo - Deslinda Syam; Endry Martius; Osmet (Jurnal Niara, 2023)
Community Based Tourism is a concept that refers to an effort that ownership, control, and benefit of tourism development is in the hands of community, so that the success of the community-based tourism doesn’t only attract domestic and international tourists to visit tourism destinations but also to dig and create business opportunity in order to increase the economy of community that leads to welfare of local community. Research was conducted in Payo located at RW 6 Tanah Garam Village Lubuk Sikarah Sub-District Solok City West Sumatera Province. The purpose of the research is to describe the development of community-based tourism at Payo Agrotourism Region and to analize community-based in developing Payo Agrotourism Region based on ownership, control, and benefit aspects. The research uses case study research design, type of the desain is descriptive, and strategy of the desain is survey within case study. The research consists of qualitative and quantitative data. Qualitative data is collected through case study strategy while quantitave data is collected through survey strategy. The Result of the research shows that the development of Payo Agrotourism Region is not community-based, based on aspects of community-based tourism that are: ownership, control, and benefit.